GRAMMATICAL MARKERS OF NOUN IN MANGGARAIAN LANGUAGE: CULTURAL LINGUISTIC PERSPECTIVES - Kletus Erom (Universitas Katolik Parahyangan, 2021)
Manggaraian Language (ML) is the main local language spoken by Manggaraian Language Speakers (MLS) in three Manggarai Regencies: Manggarai Regency, West Manggarai Regency, and East Manggarai Regency. ML has many unique verbal symbols. Among other things is Grammatical Markers of Nouns (GMN). The data were obtained through observation and interview. Data analysis applied Theory of Cultural Linguistics of Palmer resulting in identifying Verbal Symbols in forms GMN of ML and Cultural Imagery of MLS that motivates them to construct GMN. Seven verbal symbols of ML are found. The GMN functioning as the Grammatical Subject and Verb Complement. The GMN functioning as the Passive Agent. The GMN functioning as the Possessor of a possessed thing. The GMN functioning as the Host of a Verb. The GMN functioning as the Target of a Verb. The GMN functioning as Conjunction to the Second Nouns of the five grammatical functions. It is also found the derivation processes of the GMN. Three cultural imageries of MLS are found. Dividing Nouns into Common Noun and Proper Noun and Fastening different GM to them implies that Nouns are important in cultural imagery of MLS. Fastening different GM to CN and PN implies that CN and PN are different in cultural imagery of MLS. Fastening only one form of GM to CN but two forms of GM to PN implies that PN is important in cultural imagery of MLS.